PENGEMBANGAN USAHA BATIK MELALUI MESIN PEWARNAAN BATIK DI DESA PILANG KECAMATAN MASARAN KABUPATEN SRAGEN - LV. Ratna Devi S; Susantiningrum Susantiningrum (Universitas Sebelas Maret, 2017)
Pilang Village is one of the villages in Subdistrict of Sragen. This village has a potential in producing batik. Batik is a craft that has high artistic value and has been a part of Indonesian culture (especially in Java) since long. Up till now in Sragen, batik staining has been doing manually; this becomes an obstacle because manual staining takes a long time and sometimes not tidy. To overcome this, then the officials provide a dye machine batik, i.e., Fider machine. The benefits gained from the implementation of this activity are to help improve the quality of production, help develop the business of batik SME Karya Mandiri, and help improve the professionalism and productivity of batik craftsmen group, in order to achieve the formation of groups of batik craftsmen. Methods used to help overcome the problems that have been agreed above are through business management training, training and partial support of production equipment support and mentoring.